PHILOSOPHY AS AN AGORA OF CULTURAL DIALOGUE: MEETING OF MARTIN HEIDEGGER AND PAUL CELAN - Tytar, Olena Volodmyrivna; Kostenko, Ganna K.; Ovcharenko, Nataliia M. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2021)
Philosophy as poetry and praxis, as agora of cultural dialogue is considered. Based on hermeneutic analysis of one of Paul Celan’s poems (“Todtnaubeg”), the possibity of a dialogue between twentieth‐century philosophy (Martin Heidegger) and twentieth‐century poetry (Paul Celan) in the agora of public philosophizing has been established. Paul Celan was comforted by philosophy (euphrasia). It turns out that philosophy is always more than philosophers, this is the main lesson learnt by the author of the poem “Todtnaubeg”. It is shown that anthropological issues are always broader than individual discourses, although even in individual works (treatise, poem) we can find a whole rang of such discourses.The poet dedicates poem "Todtnaberg" to the turning point in his life and development of twentieth‐century philosophy (meeting with the most famous and influential twentieth‐century philosopher Martin Heidegger).Philosophy is seen as a complex combination of poetry and praxis, diverse discourses, as a place of  cultural dialogue and a therapy for cultural trauma. Paul Celan needed such consolation (euphrasia) by philosophy, and he received it from philosophy and philosophical communication in general, and not from Martin Heidegger (the reasons for distortion of communication and integrity of dialogical discourse are considered).Unfortunately, Heidegger himself was not always ready for such a dialogue, but his philosophy acts on his behalf, complementing the words of poetry, the very situation of an agora is based on freedom of philosophical thought, at the top of Mountain of the Dead or the Magic Mountain, the main thing is that they maintain humanity and openness to the Other Voice which can be heard from any top.Language provides an opportunity not only to express but also to create ‐ to reproduce the unity of the world, unity of the sacred and being, meaning of the Logos significantly deepens both the philosophy of language and the theory of performativity in the creative, therapeutic function of the Word. Logos imparts truth and comprehensiveness to the statement. This provides an opportunity for not an objective but an ontological identity which through the word reveals the unity of being, overcomes its rupture and trauma.